A Rare Occurrence of Postural Hypotension in a COVID-19 Patient - Muhammad Farooq; Riyaz Ahmad Bhat; Wejdan Alotoibi (Liaquat National Journal of Primary Care, 2022)
The SARS-CoV-2 infection has presented itself with typical presentations like other viral infections and atypical presentations as well. Many of the clinical associations are established and still, researches are ongoing. It is still an evolving disease and is an area of research at present time. We present a rare case of postural hypotension in a 49-years-old COVID-19 patient. We admitted a 49-year-old diabetic male patient with a history of acute onset of shortness of breath, cough and fever. The patient was diagnosed case of a COVID-19 infection and was admitted with mild to moderate symptoms. The patient maintained his normal saturation on oxygen. The patient developed an unusual symptom of postural hypotension during his hospital stay and it was managed with a conservative approach. The development of postural hypotension in a COVID-19 patient is reported very rarely. Given the fact that postural hypotension is an important and specific disease entity, this association presents an active area of research in the present era.